2012
DOI: 10.5586/aa.2011.027
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different nitrogen fertilization rates on yield and quality of marigold (Calendula officinalis L. 'Tokaj') raw material

Abstract: A b s t r a c tPot marigold (Calendula officinalis L.) is an annual ornamental plant which is also grown for herbal raw material (flower heads) used in the pharmaceutical and cosmetic industries. ) on some morphological features of flower heads as well as on yield and quality of pot marigold raw material. Flowering of pot marigold was shortest in the control treatment (32 days) and longest (43 days) in the plot where nitrogen fertilization had been applied at the highest rate (160 kg N×ha -1 ). Nitrogen fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 7 publications
3
19
0
Order By: Relevance
“…Hoffmann and Komosa [12] concluded likewise when discussing their experiment, in which higher NPK fertilization rates significantly increased the number of flowers and weight of herbal yield. Dedio et al [1], as well as Biesiada et al [13] conclude that calendula does not require intensive nitrogen nutrition and set the optimum dose at 30-50 kg•ha -1 . Mili and Sable [14] claim otherwise, and report the highest number of flowers after the soil enrichment with 100 kg N•ha -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Hoffmann and Komosa [12] concluded likewise when discussing their experiment, in which higher NPK fertilization rates significantly increased the number of flowers and weight of herbal yield. Dedio et al [1], as well as Biesiada et al [13] conclude that calendula does not require intensive nitrogen nutrition and set the optimum dose at 30-50 kg•ha -1 . Mili and Sable [14] claim otherwise, and report the highest number of flowers after the soil enrichment with 100 kg N•ha -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Also, Rahmani et al (2009) found that nitrogen had a significant effect on all plant parameters of C. officinalis, such as seed yield, head diameter, number of flowers carried out with application of 90 kg N ha -1 . Król, (2011) found a clear increase in yield of Calendula officinalis 'Tokaj' after the application of 80 kg N /ha, when compared to the control treatment. Also, Johnson et al (2018) found that five urea N rates (0, 34, 67, 134, or 202) kg /N ha increased significantly seed yield of C. officinalis.…”
Section: Introductionmentioning
confidence: 85%
“…All treatments showed significant increase in chlorophyll a and b content when compared to the control 1.59 and 1.57 mg/g fresh weight; 0.756 and 0.78 mg/g fresh weight, in the same respect order. Elements availability, especially nitrogen due to its external application played an important role in photosynthesized pigments formation and thus the amount of chlorophyll synthesized (Król, 2011;Hussein et al, 2011;Elhindi, 2012;Abou-Sreea et al, 2017). Chlorophyll has a cyclic tetrapyrrole ring structure termed as prophyrines which N is a basic component for it (Satish and Manju, 2018).…”
Section: -Chlorophyll a And Bmentioning
confidence: 99%
“…The flower yield of marigold was highly sensitive to nitrogen deficiency, since there was a 90% decrease in the number of flowers per plant when the plants were grown under -N treatment compared with the complete nutrient solution treatment (Table 4). In marigold (Calendula officinalis L. 'TOKAJ'), nitrogen fertilization had a significant impact on the number of flower heads per plant (especially on the second-rank branches) [9].…”
Section: Tagetes Erecta L (Marigold)mentioning
confidence: 99%